Primary cutaneous mucormycosis of the abdomen at the site of repeated insulin injections. Issue 2 (10th February 2020) - Perz, Allison; Makar, Gabriel; Fernandez, Edward; Weinstock, Joshua; Rafferty, William
Abstract : A 71-year-old woman with metastatic squamous cell carcinoma of the lung and insulin-dependent type 2 diabetes mellitus presented with a necrotic lesion on her lower abdomen. Further history revealed that this was the site of repeat insulin injections with reuse of the same needles. On investigation, biopsy of the site was positive for broad, aseptate, right-angle branching fungal hyphae consistent with mucormycosis. Studies have shown that insulin needle reuse is a common practice among diabetics for several reasons, including cost and convenience. While the current American Diabetes Association guidelines suggest that this is an acceptable practice among the general population of diabetics, they advise against it in patients who are actively ill or immunocompromised. Discussion about insulin needle reuse should be of utmost importance among providers and their diabetic patients, especially for patients who are immunocompromised.